Electric energy demand of Turkey for the year 2050 - Yumurtaci, Z; Asmaz, E (TAYLOR & FRANCIS INC, 2004)
Hydro electrical energy is the most important renewable energy resource in Turkey. Both environmental suitability and low unit energy cost are the principal reasons of its frequent use for energy production in the world, as well as in Turkey. According to the statement of DSI (State Hydraulic Works) and EIEI (Electrical Power Resources Survey and Development Administration) for the year 2002, Turkey will develop its whole hydro energy potential until the year 2050. In this study, the energy use projection of Turkey for the period of 1980-2050 is calculated based on the population increase and energy consumption increase rates per capita. The study also includes the evaluation of energy requirement in the year 2050 in the case of whole hydro energy potential usage.
Keywords: energy consumption per capita; energy demand; hydro electrical energy; thermal energy; Energy & Fuels; Engineering